Efficient optimization of pyrazolo[3, 4-d]pyrimidines derivatives as c-Src kinase inhibitors in neuroblastoma treatment. Issue 21 (15th November 2018) - Molinari, Alessio; Fallacara, Anna Lucia; Di Maria, Salvatore; Zamperini, Claudio; Poggialini, Federica; Musumeci, Francesca; Schenone, Silvia; Angelucci, Adriano; Colapietro, Alessandro; Crespan, Emmanuele; Kissova, Miroslava; Maga, Giovanni; et al.
Graphical abstract: Highlights: Synthesis of pyrazolo[3, 4- d ]pyrimidines derivatives endowed with nM Ki values. Best compound exerted good cytotoxicity activity against neuroblastoma cells. Optimization process based on SAR study and ADME profile. Abstract: The proto-oncogene c-Src is a non-receptor tyrosine kinase which is involved in the regulation of many cellular processes, such as differentiation, adhesion and survival. c-Src hyperactivation has been detected in many tumors, including neuroblastoma (NB), one of the major causes of death from neoplasia in infancy. We already reported a large family of pyrazolo[3, 4- d ]pyrimidines active as c-Src inhibitors. Interestingly, some of these derivatives resulted also active on SH-SY5Y NB cell line. Herein, starting from our previous Free Energy Perturbation/Monte Carlo calculations, we report an optimization study which led to the identification of a new series of derivatives endowed with nanomolar Ki values against c-Src, interesting antiproliferative activity on SH-SY5Y cells and a suitable ADME profile.